Maintaining faith in agency under immutable constraints: Cognitive consequences of believing in negotiable fate - AU, Evelyn Wing-Mun (Institutional Knowledge at Singapore Management University, 2011)
Negotiable fate refers to the idea that one can negotiate with fate for control, and that people can exercise personal agency within the limits that fate has determined. Research on negotiable fate has found greater prevalence of related beliefs in Southeast Asia, East Asia, and Eastern Europe than in Western Europe and English-speaking countries. The present research extends previous findings by exploring the cognitive consequences of the belief in negotiable fate. It was hypothesized that this belief enables individuals to maintain faith in the potency of their personal actions and to remain optimistic in their goal pursuits despite the immutable constraints. The belief in negotiable fate was predicted to (a) facilitate sense-making of surprising outcomes; (b) increase persistence in goal pursuits despite early unfavorable outcomes; and (c) increase risky choices when individuals have confidence in their luck. Using multiple methods (e.g., crosscultural comparisons, culture priming, experimental induction of fate beliefs), we found supporting evidence for our hypotheses in three studies. Furthermore, as expected, the cognitive effects of negotiable fate are observed only in cultural contexts where the fate belief is relatively prevalent. Implications of these findings are discussed in relation to the intersubjective approach to understanding the influence of culture on cognitive processes (e.g., CHIU, Gelfand, Yamagishi, Shteynberg, & Wan, 2010), the sociocultural foundations that foster the development of a belief in negotiable fate, and an alternative perspective for understanding the nature of agency in contexts where constraints are severe. Future research avenues are also discussed.